Energetic electron bursts in the plasma sheet and their relation with BBFs. Issue 11 (11th November 2014) - Duan, A. Y.; Cao, J. B.; Dunlop, M.; Wang, Z. Q.
Abstract We studied energetic electron bursts (EEBs) (40–250 keV) in the plasma sheet (PS) and their relation to bursty bulk flows (BBFs) using the data recorded by Cluster from 2001 to 2009. The EEBs in the PS can be classified into four types. Three types of EEBs are dispersionless, including EEBs accompanied with BBFs (V > 250 km/s) but without dipolarization front (DF); EEBs accompanied with both dipolarization front (DF) and BBF; and EEBs accompanied with DF and fast flow with V < 250 km/s. One type of EEB, i.e., EEBs not accompanied with BBFs and DFs, is dispersed. The energetic electrons (40–130 keV) can be easily transported earthward by BBFs due to the strong dawn‐dusk electric field embedded in BBFs. The DFs in BBFs can produce energetic electrons (40 to 250 keV). For the EEBs with DF and BBFs, the superposed epoch analyses show that the increase of energetic electron flux has two phases: gradual increase phase before DF and rapid increase phase concurrent with DF. In the PS around x = −18 RE, 60%–70% of EEBs are accompanied with BBFs, indicating that although hitherto there have been various acceleration mechanisms of energetic electrons, most of the energetic electrons in the PS are related with magnetic reconnection, and they are produced either directly by magnetic reconnection or indirectly by the DFs within BBFs. In the BBF's braking region of −12 RE < x < −10 RE, 20% of EEBs are accompanied with BBFs. The corresponding ratio between EEBs and BBFs shows a dawn‐dusk asymmetry.